The study of Relationship between Political Attitude of Elite Audiences and their Decoding of 20:30 News Program in Hamedan - Javad Afsharkohan; Mojtaba Hooshmandi Yavar (Taḥqīqāt-i Farhangī-i Īrān)
Although the news texts are produced by media professionals but the main subject of this article is how audiences understand and grasp them. In the other words, how the texts are understood and decoded? This research is based on a theoretical framework developed by Stuart Hall and Laclau and Mouffe'. To examine this idea, a mixed method has been used. In order to recognise how audience confront the 20:30 news program, in-depth interviews were done, and for measuring their political attitudes a questionnaires have been used. The research findings show that the audiences, who have broader access to different discourses, decode the news programs 20:30 differently. Based on their political tendencies towards conservative and liberal attitudes as well as some variables such as cultural capital, structural position and subject position in which they are located, they will decode the texts differently.